2017
DOI: 10.1002/ajcp.12202
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Teachers’ Experiences with Violence and Lack of Administrative Support

Abstract: Teacher-directed violence is a common, yet understudied, phenomenon. Perpetrators of violence against teachers include not just students, but also administrators, parents, and colleagues. Administrators are key stakeholders when it comes to shaping school climate and safety that can reduce or increase the negative impact of violence against teachers. In this study, 237 teachers' qualitative responses from a larger sample of 2,431 anonymous, online survey responses were examined to better understand their exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 45 publications
(63 reference statements)
8
57
0
2
Order By: Relevance
“…On the basis of our findings, a high percentage of education workers felt they did not receive an adequate response from administration after the event was reported. Fear of repercussion from parents, protection of the school's reputation, a lack of a consistent and effective discipline policy, and a poor relationship with administrators have been identified as some possible explanations for the lack of adequate response from administration . Consistent with previous studies, we also found that a lack of an adequate leadership response to incidents of WPV can impact education workers negatively, which then results in lower job satisfaction, burnout, teacher turnover, and professional disengagement .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On the basis of our findings, a high percentage of education workers felt they did not receive an adequate response from administration after the event was reported. Fear of repercussion from parents, protection of the school's reputation, a lack of a consistent and effective discipline policy, and a poor relationship with administrators have been identified as some possible explanations for the lack of adequate response from administration . Consistent with previous studies, we also found that a lack of an adequate leadership response to incidents of WPV can impact education workers negatively, which then results in lower job satisfaction, burnout, teacher turnover, and professional disengagement .…”
Section: Discussionsupporting
confidence: 88%
“…Fear of repercussion from parents, protection of the school's reputation, a lack of a consistent and effective discipline policy, and a poor relationship with administrators have been identified as some possible explanations for the lack of adequate response from administration . Consistent with previous studies, we also found that a lack of an adequate leadership response to incidents of WPV can impact education workers negatively, which then results in lower job satisfaction, burnout, teacher turnover, and professional disengagement . Conversely, employees who felt supported by school administration reported greater well‐being, were more likely to remain in their school, and were less exposed to violence .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Effective principals encourage collaboration, create a positive school climate, and support and motivate their teachers (e.g., Astor et al, ). When teachers do not feel adequate support from administrators following a violent incident, they may feel blamed, unsafe, or disempowered (McMahon et al, ), and less administrative support is associated with higher levels of multiple victimization (Martinez et al, ). Inaction may also suggest school leaders’ limited interest or training in generating effective solutions for aggressive incidents, which may make these issues more likely to reoccur.…”
Section: Discussionmentioning
confidence: 99%